New sound transmission challenges-a case study - McBurney, T. (Canadian Acoustics, 1997)
The focus of this paper is the sound transmission issue as it relates to revitalization and development projects in "The Kings" (two recently rezoned districts in the central area of Toronto). The preamble to the zoning changes involved a great deal of input by politicians, planners, building regulators and the development industry and the goal is to provide for revitalized development in the target districts which over the years have become rundown and under-utilized. Many of the buildings in these two districts are old abandoned industrial structures. The goal of the rezoning is to allow a broad range of mixed uses within buildings by lifting existing land-use controls which would normally restrict certain combinations of uses